Humoral and Complement Systems in Children With Acute Immune Thrombocytopenic Purpura - Hossein Karami; Javad Ghaffari; Siavash Moradi; Laleh Vahedi; Fatemeh Mohammadi-Kharkeshi (Mazandaran University of Medical Sciences, 2020)
Background: Immune thrombocytopenia (ITP) is an autoimmune disorder associated with decreased platelet production and accelerated platelet destruction. An impaired immune system may induce by or be associated with ITP.  Objectives: This study aimed to evaluate complement and humoral immune systems in ITP.  Methods: We evaluated 30 children (under 19 years old) with acute and chronic ITP referred to a tertiary hospital and compared them with 30 healthy volunteers. We assessed the samples' CBC with differentiation, serum immunoglobulins (IgG, IgE, IgM, IgA, IgG1, IgG2, IgG3, IgG4) by nephelometry, antistreptolysin O titer by agglutination, CH50, C3, C4 by nephelometry, CD19 by flow cytometry, and anti-tetanus antibody titer by ELISA. Their demographic data were obtained with a questionnaire. Results: Our findings showed that humoral and complement components were normal in both patients and healthy groups. However, based on independent t test results, the mean serum levels of IgM, IgE, IgG1, C3, and tetanus antibody levels were significantly higher in the patient group. Conclusions: Humoral and complementary immunodeficiency in these patients is unlikely. However, more studies with larger sample sizes are needed.